Prolonged oral administration of Gastrodia elata extract improves spatial learning and memory of scopolamine-treated rats - Park, Young-Mi (Lab Anim Res, 2015)
Gastrodia elata (GE) is traditionally used for treatment of various disorders including neurodegenerative diseases such as Alzheimer's disease. To investigate the neuroprotective effect of GE, amyloid-β peptide (Aβ)-treated PC12 cells were cultured with GE aqueous extract. In vitro assay demonstrated that 50 µM of pre-aggregated Aβ was lethal to about a half portion of PC12 cells and that Aβ aggregate-induced cell death was significantly decreased with GE treatment at ≤10 mg/mL in a dose-dependent manner. To further examine in vivo cognitive-improving effects, an artificial amnesic animal model, scopolamine-injected Sprague-Dawley rats, were orally administered the extract for 6 weeks followed by behavioral tests (the passive avoidance test and Morris water maze test). The results showed that an acute treatment with scopolamine (1 mg/kg of body weight) effectively induced memory impairment in normal rats and that the learning and memory capability of scopolamine-treated rats improved after prolonged administration of GE extract (50, 250 and 500 mg/kg of body weight for 6 weeks). These findings suggest that a GE regimen may potentially ameliorate learning and memory deficits and/or cognitive impairments caused by neuronal cell death.